Kingdom of the Netherlands-Aruba : Staff Report for the 2015 Article IV Consultation Discussions. (IMF Staff Country Reports; Country Report, 2015)
This 2015 Article IV Consultation highlights that Aruba has been recovering from a severe double-dip recession. The economy faced two major shocks over the past five years-the global financial crisis and shutdown of the Valero oil refinery in 2012. After a strong recovery in 2013 with growth reaching 4.75 percent, the pace of activity moderated in 2014. In 2015, growth is projected to rise to 2.25 percent. The tourism sector-the mainstay of the Aruban economy-is envisaged to grow, albeit at a slower rate. Moreover, domestic demand is slated to recover notably amid subsiding policy uncertainty and as key public-private partnership projects move forward.